2014
DOI: 10.1002/2013wr014061
|View full text |Cite
|
Sign up to set email alerts
|

Diel flow pulses drive particulate organic matter transport from microbial mats in a glacial meltwater stream in the McMurdo Dry Valleys

Abstract: [1] Many glacial meltwater streams in the McMurdo Dry Valleys (MDV) of Antarctica contain abundant microbial mats, representing hot spots of primary production in a barren landscape. These mats persist through the winter in a freeze-dried state and grow in the summer, experiencing a dynamic hydrologic regime as streamflow varies on a diel cycle and with weather conditions. During diel peaks in flow these streams transport particulate organic matter (POM) to the downstream closed-basin lakes. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…The most consistently flowing streams in the Fryxell basin are Canada, Green, Lost Seal, and Aiken, which exceed 1 l/s greater than 70% of the time and have flowed every year of the record (Figure a, b). These streams also have a greater probability of exceeding daily average flows higher than 100 l/s, which corresponds to a greater probability of high flows that would scour benthic microbial mats (Cullis et al, ). Lower median daily average discharge values are observed at Crescent (2.5 l/s), Delta (2.3 l/s), Von Guerard (1.8 l/s), Huey (0 l/s), and Harnish 0 l/s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most consistently flowing streams in the Fryxell basin are Canada, Green, Lost Seal, and Aiken, which exceed 1 l/s greater than 70% of the time and have flowed every year of the record (Figure a, b). These streams also have a greater probability of exceeding daily average flows higher than 100 l/s, which corresponds to a greater probability of high flows that would scour benthic microbial mats (Cullis et al, ). Lower median daily average discharge values are observed at Crescent (2.5 l/s), Delta (2.3 l/s), Von Guerard (1.8 l/s), Huey (0 l/s), and Harnish 0 l/s.…”
Section: Resultsmentioning
confidence: 99%
“…When streamflow ceases in the fall, the microbial mats become freeze‐dried and then resume photosynthetic production within hours of becoming wetted with the initiation of flow the next summer (Niyogi et al, ; McKnight et al, ). The distribution and abundance of microbial mats are controlled by habitat and long‐term flow regime, with losses occurring because of scour under high flows and desiccation under several years of low flows (Cullis et al, ; Kohler et al, ). In turn, changes in mat abundance may alter nutrient loading to the lakes because the mats mediate in‐stream nutrient cycling (McKnight et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in peak daily discharge and in the intensity of diurnal discharge variation through the melt season, which also drives high rates of sediment delivery (Perolo et al, 2019), leads to the morphodynamically most active period. Not only may such activity erode the sediments to which biofilms are bound, the high sediment transport rate (Milner & Petts, 1994), and flow shear stresses (Cullis, Stanish, & McKnight, 2014) may scour biofilms from bed sediments. Because disturbances are frequent, biofilms cannot fully develop and they cannot impact stream habitability.…”
Section: Active Floodplainmentioning
confidence: 99%
“…If there is more abundant fine sediment in the channel, the magnitude of flow required for a "re-setting" scouring event may be lower, e.g. potentially lower than the 100 L s −1 threshold used by Cullis et al (2014) in their model. The lower limit for a re-setting flow may be determined by the flow required to keep introduced sediment entrained in the reaches where the microbial mats thrive.…”
Section: Implications For Stream Ecosystemsmentioning
confidence: 99%
“…Kohler et al (2015b) specifically focused on epilithon responses from scour events, noting that recovery times were generally weeks to months, potentially longer than a single flow season. Furthermore, Cullis et al (2014) showed that the daily transport of particulate organic matter (POM) from sloughing driven by fluvial shear stress was limited by the availability of "mobile biomass" associated with the mats. However, at high flow the hysteretic pattern associated with such a limitation was not observed and direct scour of the mats appeared to be the dominant mechanism controlling POM transport.…”
Section: Implications For Stream Ecosystemsmentioning
confidence: 99%